Learning Difficulties of Grade IV Students in the IPAS Subject of the Merdeka Curriculum - Zahra, Avivah; Khairiyah, Nizfa; Anihsa, Anihsa; Wardani, Anggita Cahya; Rulfani, Amelia Reski; Amelia, Citra; Reinita, Reinita; Salmaini, Salmaini (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
This study aims to analyze the learning difficulties faced by students in the subject of Natural and Social Sciences (IPAS) within the implementation of the Merdeka Curriculum. Through a literature review of various sources, it was found that students encounter challenges in understanding abstract concepts that integrate aspects of both natural and social sciences. Factors contributing to these learning difficulties include low motivation, limited learning media, a lack of varied teaching strategies, and the suboptimal role of teachers in applying appropriate learning approaches. To address these issues, collaboration among teachers, students, and parents is essential, along with enhancing teachers' competencies in developing adaptive and engaging teaching methods. Thus, it is hoped that IPAS learning can proceed more effectively and enjoyably, thereby improving students' understanding and skills in line with the objectives of the Merdeka Curriculum.